A Facile Strategy for the Ion Current and Fluorescence Dual-Lock in Detection: Naphthalic Anhydride Azide (NAA)-Modified Biomimetic Nanochannel Sensor towards H2S - I Wu (MDPI AG, 2021)
Inspired by biological channels, the electric signal-based artificial nanochannel system exhibits high sensitivity in various analyses. However, ion current may be affected by many other factors, leading to false-positive signals. For reliable detection, in this work, we apply a facile strategy to combine both current signal and fluorescence. Fluorescent probes were conjugated to the nanochannel surface by covalent bonds. By utilizing the specific reduction of azide groups in the probe to amino groups by H2S, a synchronizing change in fluorescence and nanochannel surface charge was established. As a result, both transmembrane ion current and fluorescence intensity showed significant changes. The photoelectric double-checked locking from temporal and spatial variation validly confirmed the response process and protected detection accuracy. The work may provide new ideas for the development of more sophisticated current and fluorescence dual-index nanochannel systems.